Design, synthesis, and anti-influenza activity of substituted quercetins and progress towards the synthesis of mini graphenes like hexa-peri-benzocoronene cyclophane - Thapa, Mahendra (Kansas State University, 2012)
The first chapter of the thesis involves the design, synthesis, and anti-influenza activity of quercetin derivatives. Influenza viruses are important pathogens that cause respiratory infections in humans and animals. In addition to vaccination, antiviral drugs against influenza virus play a significant role in controlling viral infections by reducing disease progression and virus transmission. Plant derived polyphenols are associated with antioxidant activity, anti-carcinogenic, and cardio- and neuro-protective actions. Some polyphenols, such as resveratrol and epigallocatechin gallate (EGCG), showed significant anti-influenza activity in vitro. The antiviral effects of isoquercetin were greater than that of quercetin with lower IC[subscript]5[subscript]0 values and higher in vitro therapeutic index. Various phenolic esters, alkoxy and aminoalkoxy derivatives of quercetin were synthesized by functionalization of C3, C3’, and C5 hydroxyl groups. Antiviral activities of these synthesized compounds were tested against influenza virus (porcine H1N1 strain). Quercetin-3-gallate which is structurally similar to EGCG showed greater antiviral activity among the synthesized compounds. Its antiviral activity was comparable to that of EGCG with better in vitro therapeutic index. Second chapter in the thesis involves the progress towards the synthesis of mini graphenes like hexa-peri-benzocoronene cyclophane (HBCC). Bilayered graphenes are highly conducting materials with potential application in electronic devices and in lithium ion batteries. Despite great potential, bilayer graphenes with defined distance between the two layers have not been achieved through chemical synthesis. Chemical synthesis of hexa-peri-benzocorenene cyclophane (HBCC) from commercially available p-xylene was carried out. Final product, presumably compound 90 (the structure has not been completely characterized), is insoluble in all tested solvents including aqueous acids and organic solvents such as DMSO, DMF, benzene, 1,2-dichlorobenzene, dichloromethane, THF, hexanes and diethyl ether. The insoluble nature of the final product restricted the analysis to UV-visible spectroscopy. Synthesis of soluble analog incorporating the long chain ether groups is being investigated in Dr. Hua’s laboratory.
Keywords: Quercetin; Anti-influenza; Carbon nanotubes; Hexabenzocoronenes; Chemistry (0485)